Book Reviews - Judy Halden-Sullivan; Julie J. Nichols; Mary Pettice (Journal of the Assembly for Expanded Perspectives on Learning, 2011)
Book Reviews Judy Halden-Sullivan - Evolution and Criticism Julie J. Nichols - Boyd, Brian. On the Origin of Stories: Evolution, Cognition, and Fiction. Cambridge: Belknap Press of the Harvard University Press, 2009. Julie J. Nichols - Zunshine, Lisa. Why We Read Fiction: Theory of Mind and the Novel. Columbus: Ohio State University Press, 2006 Mary Pettice - Dutton, Denis. The Art Instinct: Beauty, Pleasure, and Human Evolution. 2nd edition. New York: Bloomsbury Press, 2010. Print.